Effect of serological status of the Bovine Leucosis Virus (BLV) on milk production of dairy herds in Costa Rica (Ciencias Veterinarias, 2014)
A longitudinal study was conducted in order to determine the effect of serological status of the Bovine Leucosis Virus (BLV) on milk production of specialized dairy herds in Costa Rica. The serological status and milk production were analyzed in 1719 cows of 26 farms during two lactation periods. An immunoenzymatic assay (ELISA) was used to confirm the serological status of the animals’ BLV. Production records were taken from the VAMPP Bovino database. Cows were grouped in three categories: 999 seronegative subjects, 152 seroconverted during the study and 568 seropositive subjects during the entire period of study. By means of the Kruskal-Wallis test, the combined effect of the serostatus per breed and lactation number was calculated on the 305-day milk production (kg 305-d). In addition, the effect of serostatus corrected by herd, breed and lactation number was assessed using a mixed linear regression model. The risk that a seroconverted or seropositive cow reduced its milk production was assessed by logistic regression. Significant differences in kg 305-d were found in seroconverted cows with 1-2 lactations (P= 0.005) and seropositive cows with 3-5 lactations (P= 0.006). Comparing kg 305-d per breed, a significant difference was determined in Holstein and Jersey cows (P